2014
DOI: 10.3945/jn.113.178715
|View full text |Cite
|
Sign up to set email alerts
|

Absorbed Zinc and Exchangeable Zinc Pool Size Are Greater in Pakistani Infants Receiving Traditional Complementary Foods with Zinc-Fortified Micronutrient Powder

Abstract: Adequacy of zinc intake from breast milk alone becomes marginal in relation to infant requirements by around 6 mo of age. Simple and cost-effective strategies are needed at the population level to ensure adequate intakes of zinc in infants and toddlers in populations at risk of zinc deficiency. We determined the amount of absorbed zinc (AZ) from a micronutrient powder (MNP) without and with 10 mg of zinc (MNP+Zn) added to local complementary foods used in Pakistan and the impact on the exchangeable zinc pool (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…With a sample size of 58 children per sub-group (i.e., 174 children total), we will have 80% power to detect a difference in EZP size of 0.67 mg/kg body weight, assuming a one-sided test, alpha of 0.05, standard deviation of 1.2, and potential loss of 15% of samples due to attrition or sampling errors. This effect size is consistent with findings from a study of zinc supplementation in Pakistani infants, which reported an effect size of 0.8 mg/kg body weight for EZP size [ 22 ].…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…With a sample size of 58 children per sub-group (i.e., 174 children total), we will have 80% power to detect a difference in EZP size of 0.67 mg/kg body weight, assuming a one-sided test, alpha of 0.05, standard deviation of 1.2, and potential loss of 15% of samples due to attrition or sampling errors. This effect size is consistent with findings from a study of zinc supplementation in Pakistani infants, which reported an effect size of 0.8 mg/kg body weight for EZP size [ 22 ].…”
Section: Methodssupporting
confidence: 90%
“…Participants assigned to study group 3 will consume the high-zinc, low-iron MNP formulation and a high-zinc, no-iron MNP formulation on alternating days (i.e., on day 1 consumes high-zinc, low iron MNP formulation then on day 2 will consume high zinc, no iron MNP formulation, then on day 3 again the same formulation as on day 1 and so on) to determine the impact of giving iron and zinc on alternate days on growth and diarrhea prevention. Since several studies have documented the positive impact of preventive zinc supplementation in the form of a dispersible tablet [ 3 , 22 ], study group 4 will receive a 10 mg dispersible zinc tablet, which will serve as the positive control. Study group 5 will assess whether intermittent consumption of 10 mg of preventive zinc supplements for 14 days immediately following enrolment, for 14 days at 3 months and placebo tablets on all other days’ results in sustained benefits on diarrhea prevention and growth.…”
Section: Methodsmentioning
confidence: 99%
“…Although much of zinc is not accessible to measurement in the body due to its incorporation into proteins and function in cellular processes, ∼20% of body zinc exchanges rapidly with plasma and is called the exchangeable zinc pool or EZP, which has been suggested as a biomarker of zinc status ( 22 ). One study determined the change in EZP after supplementation, where it was responsive ( 105 † ). Further research on the topic is warranted because EZP could prove to be a more robust estimate of zinc stores than plasma concentrations alone.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…An example of zinc fortification is point-of-use fortification by including zinc in micronutrient powders that are added to traditional foods shortly before consumption. In a trial in Pakistani infants, total absorbed zinc from a zinc-containing micronutrient powder sprinkled on rice and lentils increased when compared with a control powder (1.2 ± 0.5 and 0.1 ± 0.1 mg, respectively) and the EZP was enhanced (4.5 ± 1.0 and 3.7 ± 0.6 mg/kg, respectively) ( 105 † ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…These studies provide useful information on zinc metabolism and homeostasis to assist in providing optimal zinc supplements for maximum benefits. Such studies address the effect of zinc dose [ 146 , 147 , 148 ], fortification with zinc [ 132 , 149 ] habitual diets [ 37 , 43 ] and avoiding high phytate diets [ 36 , 73 , 150 , 151 , 152 ] However, there are no studies to date applying zinc stable isotope techniques to assess zinc metabolism and homeostasis in children in low-middle income countries with acute diarrhoea. Further, there is only one study on environmental enteropathy [ 43 ].…”
Section: Implications For Zinc Supplementationmentioning
confidence: 99%